2008
DOI: 10.1021/la801766y
|View full text |Cite
|
Sign up to set email alerts
|

Complex Langmuir−Blodgett Films of SiO2 and ZnO Nanoparticles with Advantageous Optical and Photocatalytical Properties

Abstract: Multifunctional Langmuir-Blodgett (LB) films were fabricated on the surface of glass substrates using sol-gel derived ZnO and SiO2 particles. ZnO particles of 6 and 110 nm diameter were synthesized according to the methods of Meulenkamp and Seelig et al. (Meulenkamp, E. A. J. Phys. Chem. B 1998, 102, 5566; Seelig, E. W.; Tang, B.; Yamilov, A.; Cao, H.; Chang, R. P. H. Mater. Chem. Phys. 2003, 80, 257). Silica particles of 37 and 96 nm were prepared by the Stober method (Stober, W.; Fink, A.; Bohn, E. J. Colloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…The LB deposition of multilayers is a relatively rapid process which is well suited for applications that do not require films with a perfect crystalline microstructure. Nagy et al described recently antireflective properties of LB multilayers 63. Presently, we are studying the influence of LB deposition of antireflective coatings onto the efficiency of solar cells based on polycrystalline Si.…”
Section: From Laboratory Bench To Production Line?mentioning
confidence: 98%
See 1 more Smart Citation
“…The LB deposition of multilayers is a relatively rapid process which is well suited for applications that do not require films with a perfect crystalline microstructure. Nagy et al described recently antireflective properties of LB multilayers 63. Presently, we are studying the influence of LB deposition of antireflective coatings onto the efficiency of solar cells based on polycrystalline Si.…”
Section: From Laboratory Bench To Production Line?mentioning
confidence: 98%
“…Nagy et al described complex structures made of the sequence of layers of the SiO 2 and ZnO nanoparticles that show both photocatalytic and antireflection properties 63…”
Section: Deposition Of Complex Multilayersmentioning
confidence: 99%
“…Antireflective coatings are routinely designed to enhance the light transmission through these surfaces. 15,[32][33][34][35][36][37][38][39][40][41][42] However, antireflective coatings on flexible substrates are still rare. 32 An antireflective coating is based on destructive interference between the reflected light from the air/ film and the substrate/film interfaces.…”
Section: Stable Antireflective Property Of Filmsmentioning
confidence: 99%
“…28,29 Nagy et al synthesized multifunctional LB¯lms on the surface of glass substrates using solÀgel derived ZnO and SiO 2 particles, and found that LB method was an e±cient technique for the tailoring of complex layer structures. 30 Ikegami et al demonstrated the formation of ionic bonds between a fatty-acid of LB monolayer and a ZnO-based transparent electrode used as a substrate, which might lead to a new way of obtaining functional organicÀinorganic nanosystems. 31 Wang and Wee deposited smooth and homogeneous monolayer silicalite seeds on silicon substrate surface using LB method, noting that the seed layers were the important paramount of the thickness, smoothness and continuity of monolayer.…”
Section: Introductionmentioning
confidence: 99%